1998
DOI: 10.1117/12.332874
|View full text |Cite
|
Sign up to set email alerts
|

Resist charging in electron-beam lithography

Abstract: Electron beam exposure of masks and wafers results in charging of the insulating resist film. This charging results in an electric field which deflects incoming electrons and can be a serious source of pattern placement error in electron-beam lithography. In earlier work (Ingino et al. 1992) the surface potential was found to be positive or even zero under certain conditions. In this study, a model is developed to explain this effect and the surface potential is measured by an independent method, a Kelvin prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is known that these various types generate different levels of external field enhancement. There might even be positive charge accumulation as discovered by Bai et al 3 However, we observed SFE at primary beam energies of up to 20 kV [ Fig. At 2 kV and below (the experiment was done at 2 kV, 1 kV, and 500 V), SFE was very hard to obtain on most of the nanotubes, even though the nanotubes were observed clearly (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…It is known that these various types generate different levels of external field enhancement. There might even be positive charge accumulation as discovered by Bai et al 3 However, we observed SFE at primary beam energies of up to 20 kV [ Fig. At 2 kV and below (the experiment was done at 2 kV, 1 kV, and 500 V), SFE was very hard to obtain on most of the nanotubes, even though the nanotubes were observed clearly (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Various papers based on Monte Carlo simulations have been reported on scattering by electron irradiation. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Our measurements of surface potentials with an electrostatic force microscope (EFM) confirmed the presence of a potential distribution of the order of several V even a few mm away from the EB exposure point. Deviations of tens of nm from the design position of the exposure point due to this potential have been reported to be serious.…”
Section: Introductionmentioning
confidence: 74%
“…There are only a few reports that directly measured the surface potential distribution, and the results with a spatial resolution of several millimeters are published around 1998 by a group led by Pease of Stanford University [11]. Figure 1 shows the schematic diagram of our EFM system installed in our scanning electron microscope (SEM) specimen chamber.…”
Section: Methodsmentioning
confidence: 99%